Transparency, Price Informativeness, and Stock Return Synchronicity: Theory and Evidence - Dasgupta, Sudipto; Gan, Jie; Gao, Ning (Journal of Financial and Quantitative Analysis, 2010)
This paper argues that, contrary to the conventional wisdom, stock return synchronicity (or R 2 ) can increase when transparency improves. In a simple model, we show that, in more transparent environments, stock prices should be more informative about future events. Consequently, when the events actually happen in the future, there should be less “surprise” (i.e., less new information is impounded into the stock price). Thus a more informative stock price today means higher return synchronicity in the future. We find empirical support for our theoretical predictions in 3 settings: namely, firm age, seasoned equity offerings (SEOs), and listing of American Depositary Receipts (ADRs).